Mechanism and genesis of Sanmen Bay as a sink of Holocene Yangtze River sediment, Zhejiang Province, China - Qiu, Jiandong; Jiang, Shenghui; Wang, Jianqiang; Feng, Jing; Chen, Junbing; Dong, Chao; Jiang, Yunshui; Zhang, Daolai (Frontiers in Earth Science, 2024)
The Holocene mud deposits that extend from the Yangtze River mouth to the Taiwan Strait along the Zhejiang-Fujian coast, East China Sea (ECS), have attracted considerable research attention. However, there is a lack of consensus regarding the redistribution flux of Yangtze River sediment after it enters the sea. There are many bays along the Zhejiang and Fujian coasts, but their role in the source-sink process of Yangtze River sediment is not well-documented owing to limited data. Methods: In this study, data from shallow seismic profiles, core samples, and surface sediment samples were analysed to assess the role of Sanmen Bay, the second largest bay in Zhejiang Province, in the source-sink process of Yangtze River sediments.The results showed that Sanmen Bay is an important sink for Yangtze River sediments. The characteristics of the clay minerals indicate that the fine-grained sediments in Sanmen Bay are mainly derived from Yangtze River sediments. The thickness of Holocene deposits in Sanmen Bay ranges from 8.2 to 32.0 m, with an average of 23.4 m and a total sediment volume of 5.06 × 10 4 Mt, accounting for 1% of Yangtze River sediment in this time period. The Bayesian age-depth model based on borehole accelerator mass spectrometry (AMS) 14 C dating shows that a high sedimentation rate occurred in the early and late Holocene but decreased significantly in the mid-Holocene, which is similar to that of the inner shelf of the East China Sea (ECS). Conclusions: The variation in the Holocene sedimentation rate in Sanmen Bay is related to the southward transport process and mechanism of Yangtze River sediments. The results of this study provide a basis for understanding the source-sink process of sediment in large rivers.